200 °C annealed combinatorially deposited chalcogenide based metallic thin films for photovoltaics. (March 2015) - Ali, Nisar; Ahmed, R.; ul Haq, Bakhtiar; Shaari, A.; Jabeen, Musarrat
Abstract : Graphical abstract: Highlights: It is a new material used in photovoltaic. Combinatorial method is used for the 1st time in solar cells. The material is photoconductive in the visible and near infrared region. Having n-type conductivity. Tunable band gap. Abstract: Thin film library of tin antimony sulphide was synthesized via combinatorial thermal deposition technique on soda lime silica glass slides by two source methods. Two baffles were used for controlling the combinatorial growth. The combinatorial library was annealed in argon atmosphere inside glass ampoules at 200 °C. From the XRD spectra, the polycrystalline structure was confirmed according to JCPDS file number 34-0610. Photoconductivity response of the films was measured via photoconductivity spectrometer. The library have no transmittance lower than 720 nm. The band gap lies in the range of 1.38–2.8 eV. The thickness of the film is 15, 000 Å measured by quartz crystal monitor.